Feeding Unprotected CLA Methyl Esters Compared to Sunflower Seeds Increased Milk CLA Level but Inhibited Milk Fat Synthesis in Cows - Dohme-Meier, F. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2012)
An experiment was conducted to compare the effect of the same amount of 18:2 offered either as 18:2n-6 or as a mixture of unprotected 18:2c9t11 and 18:2t10c12 on feed intake, milk components as well as plasma and milk fatty acid profile. Fifteen cows were blocked by milk yield and milk fat percentage and within block assigned randomly to 1 of 3 treatments (n = 5). Each cow passed a 12-d adjustment period (AP) on a basal diet. After the AP cows received 1 of 3 supplements during an 18-d experimental period (EP). The supplements contained either 1.0 kg ground sunflower seeds (S), 0.5 kg conjugated linoleic acid (CLA)-oil (C) or 0.75 kg of a mixture of ground sunflower seeds and CLA-oil (2:1; SC). All 3 supplements contained the same amount of 18:2 either as CLA (∑18:2c9t11+18:2t10c12, 1:1) or as 18:2c9c12. During the last 2 d of AP and the last 4 d of EP feed intake and milk yield were recorded daily and milk samples were collected at each milking. Blood samples were collected from the jugular vein on d 11 of AP and d 15 and 18 of EP. The 18:2 intake increased in all treatments from AP to EP. Regardless of the amount of supplemented CLA, the milk fat percentage decreased by 2.35 and 2.10%-units in treatment C and SC, respectively, whereas in the treatment S the decrease was with 0.99%-unit less pronounced. Thus, C and SC cows excreted daily a lower amount of milk fat than S cows. The concentration of trans 18:1 in the plasma and the milk increased from AP to EP and increased with increasing dietary CLA supply. While the concentration of 18:2c9t11 and 18:2t10c12 in the plasma and that of 18:2t10c12 in the milk paralleled dietary supply, the level of 18:2c9t11 in the milk was similar in C and CS but still lower in S. Although the dietary concentration of CLA was highest in treatment C, the partial replacement of CLA by sunflower seeds had a similar inhibitory effect on milk fat synthesis. Comparable 18:2c9t11 levels in the milk in both CLA treatments implies that this isomer is subjected to greater biohydrogenation with increasing supply than 18:2t10c12. The fact that unprotected 18:2t10c12 escaped biohydrogenation in sufficient amounts to affect milk fat synthesis reveals opportunities to develop feeding strategies where reduced milk fat production is desirable or required by the metabolic state of the cow.